eCM 2015
DOI: 10.22203/ecm.v029a20
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biological response to extracorporeal shockwave therapy in human tendinopathy

Abstract: Extracorporeal shock wave therapy (ESWT) is a noninvasive treatment for chronic tendinopathies, however little is known about the in-vivo biological mechanisms of ESWT. Using microdialysis, we examined the real-time biological response of healthy and pathological tendons to ESWT. A single session of ESWT was administered to the mid-portion of the Achilles tendon in thirteen healthy individuals (aged 25.7 ± 7.0 years) and patellar or Achilles tendon of six patients with tendinopathies (aged 39.0 ± 14.9 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 82 publications
(59 reference statements)
1
84
2
1
Order By: Relevance
“…In animal and in vivo experiments, some studies have reported that ESWT stimulated the ingrowth of neovascularization at the tendon-bone junction and promoted the inflammatory and catabolic processes [15, 16]. Others have demonstrated that ESWT significantly decreased the nonmyelinated sensory fibers and increased tenocyte proliferation, collagen synthesis, glycosaminoglycan (GAG) content, protein synthesis, and transforming growth factor- (TFG-) β 1 [1719].…”
Section: Discussionmentioning
confidence: 99%
“…In animal and in vivo experiments, some studies have reported that ESWT stimulated the ingrowth of neovascularization at the tendon-bone junction and promoted the inflammatory and catabolic processes [15, 16]. Others have demonstrated that ESWT significantly decreased the nonmyelinated sensory fibers and increased tenocyte proliferation, collagen synthesis, glycosaminoglycan (GAG) content, protein synthesis, and transforming growth factor- (TFG-) β 1 [1719].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific biological mechanisms by which it induces therapeutic effects on pathological tendon tissue are not completely elucidated. Evidence from a recent study of human tendons suggested that the mechanical stimulus of ESWT aids tendon remodeling by promoting inflammatory and catabolic processes that are associated with the removal of damaged matrix constituents 42. In vitro studies have further suggested that ESWT increases tendon healing through the stimulation of cell proliferation and motility, neovascularization, and expression of critical differentiation genes 43.…”
Section: Discussionmentioning
confidence: 99%
“…How ESWT works is still poorly understood, but it is known to cause selective dysfunction of sensory unmyelinated nerve fibers, alteration in the dorsal root ganglia, and cavitation in interstitial and extracellular disruption, which could promote the healing response [74]. Recently, an in vivo study found that mechanical stimulus provided by ESWT might aid the initiation of tendon regeneration in tendinopathy by promoting proinflammatory and catabolic processes that are associated with removing damaged matrix constituents [75]. In recent research, series randomized placebo-controlled trials have confirmed the high evidence of efficacy of ESWT in chronic Achilles tendinopathy [74].…”
Section: Treatmentmentioning
confidence: 99%